2015
DOI: 10.3389/fnhum.2015.00212
|View full text |Cite
|
Sign up to set email alerts
|

The color red attracts attention in an emotional context. An ERP study

Abstract: The color red is known to influence psychological functioning, having both negative (e.g., blood, fire, danger), and positive (e.g., sex, food) connotations. The aim of our study was to assess the attentional capture by red-colored images, and to explore the modulatory role of the emotional valence in this process, as postulated by Elliot and Maier (2012) color-in-context theory. Participants completed a dot-probe task with each cue comprising two images of equal valence and arousal, one containing a prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 95 publications
2
40
0
5
Order By: Relevance
“…For example, the color red degrades performance in achievement contexts (e.g., tests; Elliot et al, 2007; Maier et al, 2008), red cues can interact with the emotional valence of stimuli to modulate responses to emotional stimuli (Kuniecki et al, 2015), and females who wear red clothing are rated as being more attractive and as having more sexual intent by heterosexual males, suggesting that red may act as a sexual cue (e.g., Guéguen, 2012; Elliot et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…For example, the color red degrades performance in achievement contexts (e.g., tests; Elliot et al, 2007; Maier et al, 2008), red cues can interact with the emotional valence of stimuli to modulate responses to emotional stimuli (Kuniecki et al, 2015), and females who wear red clothing are rated as being more attractive and as having more sexual intent by heterosexual males, suggesting that red may act as a sexual cue (e.g., Guéguen, 2012; Elliot et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The color red captures and holds attention in both positive and negative nonhuman stimuli, but not in neutral stimuli. In one study, this resulted in motor responses to the target stimuli being affected by attention lingering over the position where a red cue was flashed (Kuniecki, Pilarczyk, & Wichary, 2015). The same process might influence studies with facial stimuli.…”
Section: Types Of Stimulimentioning
confidence: 99%
“…The positions of electrodes are based on the international 10-20 system. The montage includes 8 midline sites (FPZ,FZ,FCZ,CZ,CPZ,PZ,POZ,OZ), 27 left hemisphere sites (FP1,AF3,F1,F3,F5,F7,FC1,FC3,FC5,FT7,C1,C3,C5,T7,CP1,CP3,CP5,TP7,P1,P3,P5,P7,PO3,PO5,P O7,O1,CB1), and 27 right hemisphere sites (FP2,AF4,F2,F4,F6,F8,FC2,FC4,FC6,FT8,C2,C4,C6,T8,CP2,CP4,CP6,TP8,P2,P4,P6,P8,PO4,PO6,P O8,O2,CB2) [11]. To avoid the external disturbance, the tip of the nose is the reference for all electrodes and the blink response of the subjects is monitored by the Vertical-Electrooculogram …”
Section: Experimental Data Acquisitionmentioning
confidence: 99%
“…Noble [10] observed that the children in higher income family had the advantages of cognitive abilities throughvarious neurocognitive systems. Kuniecki [11] proved that the red color was more capable to attract people's attention by the observation of EEG, especially in given context.…”
Section: Introductionmentioning
confidence: 99%